The subtle substances of living: Choreographies of becoming between feminist perspectives and queer temporalities (Itinera, 2023)
In the following text, I will try to articulate a thought on inhabiting from bodily practices. What I am interested in is demonstrating how a certain feminist thought in architecture in contact with performativity studies that are inextricably intertwined with questions of the production of gender and space, in nurturing each other, inaugurate a field of inquiry into the multiple modes of dwelling and their making. To do so, I will briefly traverse the trajectories of feminist thought and practice in architecture, focusing primarily on the European space and then moving geographically across the Atlantic to the epistemological openings that queer theories and practices have made on the theme of the relationship between bodies, architectures, and objects to the Caribbean. This shift will take us beyond the building, not only into urban space but especially into the dimension of the ecosystem in which Cecilia Bengolea’s choreographic works are grafted, which I will get to at the end. The material mobilized here starts from the thought produced by figures formed within the architectural sphere and in neighboring fields, but which has operated a movement of convergence with additional practices and theories from other experiences, such as performance art, feminism, and activism, bypassing disciplinary boundaries.
Keywords: architecture, performativity, queer feminism, choreography.